Subretinal fluid in eyes with active ocular toxoplasmosis observed using spectral domain optical coherence tomography. - Yanling Ouyang; Fuqiang Li; Qing Shao; Florian M Heussen; Pearse A Keane; Nicole Stübiger; Srinivas R Sadda; Uwe Pleyer (PLoS ONE)
Purpose To describe the clinical finding of subretinal fluid (SRF) in the posterior pole by spectral domain optical coherence tomography (SD-OCT) in eyes with active ocular toxoplasmosis (OT). Design Retrospective case series. Participants Thirty-nine eyes from 38 patients with active OT [corrected].. Methods Eyes with active OT which underwent SD-OCT were reviewed. SRFs in the posterior pole were further analyzed. Main outcome measures Presence of SRF; its accompanying features, e.g. retinal necrosis, cystoid macular edema (CME), choroidal neovascularization (CNV); and longitudinal changes of SRF, including maximum height and total volume before and after treatment. Results SRF presented in 45.5% (or 15/33) of eyes with typical active OT and in 51.3% (or 20/39) of eyes with active OT. The mean maximum height and total volume of SRF were 161.0 (range: 23-478) µm and 0.47 (range: 0.005-4.12) mm3, respectively. For 12 eyes with SRF related to active retinal necrosis, SRF was observed with complete absorption after conventional anti-toxoplasmosis treatment. The mean duration for observation of SRF clearance was 33.8 (range: 7-84) days. The mean rate of SRF clearance was 0.0128 (range: 0.0002-0.0665) mm3/day. Conclusions SRF (i.e., serous retinal detachment) is a common feature in patients with active OT when SD-OCT is performed. The majority of SRF was associated with retinal necrosis and reacted well to conventional therapy, regardless of total fluid volume. However, SRF accompanying with CME or CNV responded less favorably or remained refractory to conventional or combined intravitreal treatment, even when the SRF was small in size.